Serum calcium and long-term outcome after ischemic stroke: Results from the China National stroke registry III. (May 2021) - Zhang, Jun-Fang; Meng, Xia; Jing, Jing; Pan, Yuesong; Wang, Yi-Long; Zhao, Xing-Quan; Lin, Jin-Xi; Han, Xin-Sheng; Song, Bin-Bin; Jia, Zheng-Chang; Wu, Song-Di; Chen, Xiao-Fei; et al.
Abstract: Background and aims: Serum calcium abnormality is associated with adverse cardiovascular outcomes, but the effects of serum calcium level on stroke outcomes remain unknown. We aimed to assess the relationship between serum calcium level and 1-year outcomes in patients with acute ischemic stroke and transient ischemic attack. Methods: We included 9375 stroke patients from the China National Stroke Registry III for analysis. Participants were divided into 4 groups according to albumin corrected-calcium quartiles. Composite end point comprised recurrent stroke, myocardial infarction, other ischemic vascular events, and all-cause mortality. Multivariable Cox or logistic regression was used to evaluate the independent association of albumin corrected-calcium with all-cause mortality, recurrent stroke, composite end point, and poor functional outcome (modified Rankin Scale score ≥3). Results: Compared with the lowest calcium quartile (<2.16 mmol/L), the adjusted hazard ratio (95% CI) of the top quartile (≥2.31 mmol/L) was 1.56 (1.11–2.18) for all-cause mortality, 1.06 (0.87–1.28) for recurrent stroke and 1.08 (0.90–1.01) for composite end point, and the adjusted odds ratio for poor functional outcome was 1.18 (0.96–1.44). The addition of serum calcium to conventional risk factors improved risk prediction of all-cause mortality, leading to a small but significant increase in C-statistics and reclassification with non-significant integrated discrimination improvement (C-statistics, p = 0.02; net reclassification index 11.8%, p = 0.038; integrated discrimination improvement 0.08%, p = 0.42). Conclusions: High serum calcium levels at baseline were associated with all-cause mortality at 1-year after ischemic stroke, suggesting that serum calcium may be a potential prognostic biomarker and therapeutic target for ischemic stroke. Graphical abstract: Image 1 Highlights: This large multicenter cohort study investigates the association between serum calcium and outcome after ischemic stroke. In this prospective study, we found high calcium level was associated with all-cause mortality. Our data suggest that serum calcium may be a potential prognostic biomarker for ischemic stroke.